MOSQUE RUG STERILIZATION ROBOT USING ULTRAVIOLET C LIGHT WITH INTERFACE HC-05 AND ULTRASONIC - Fifi Safitri; Muhammad Amin; Iin Almeina Lubis (Informatika, Universitas Jenderal Soedirman, 2022)
Many efforts have been made to minimize the spread of the Covid-19 virus in various fields of activity including worship activities where the five daily prayers are the obligations of Muslims. When you want to pray, prayer rugs are one of the media to perform prayers so that prayers are more solemn. The prayer rug itself is one of the places where the Covid-19 virus spreads and mosque administrators only carry out prayer rug cleaning activities using a broom and washing prayer rugs. The right solution to minimize the virus that is in mosque prayer rugs is to apply the sterilization of prayer rugs on a scheduled basis. The purpose of this research is to find out how the sterilization robot works in mosque prayer mats, can design a remote control via Arduino using the HC-05 sensor, and the prayer mat sterilization robot is effective and efficient to implement. The results of this study are a robot that can be controlled via an android application that is connected via HC-05 where mosque administrators only need to control via a smartphone at one point. The method used in this study is a descriptive method where prior to conducting the research an interview was conducted regarding the circumstances to be studied, namely the cleanliness of the mosque in the use of prayer mats. It is hoped that this research can ease the work of mosque administrators and minimize time in sterilization activities and can minimize viruses that are in mosque prayer mats.